College accounting - Price, John Ellis (McGraw-Hill/Irwin, 2007)
Price/Haddock/Brock has been a long-time market leader because of its readability and relevance. The book includes many real-world examples, high-interest problems and activities, in-text help, and classroom-tested dynamic pedagogy. With the addition of McGraw-Hill's Homework Manager, Topic Tackler Plus, and an Algorithmic Test Bank, the new edition includes more technology support than ever before